STRUCTURE, MECHANICAL PROPERTIES, AND OXIDATION RESISTANCE OF MN-RICH FE-MN-AL ALLOYS - Desiati, Resetiana Dwi; Sutiawan, Edi; Sudiro, Toto; Hermanto, Bambang (National Research and Innovation Agency (BRIN), 2022)
In this study, Mn-rich Fe-Mn-Al alloys with different Al content (Al = 0, 3, and 5 % by weight) were fabricated from ferromanganese lumps using a conventional powder metallurgy technique. The samples were compacted in 1 cm steel dies using a load of 8 tons and then sintered at 1100 °C for 2 h in a tubular furnace under a vacuum condition of around 0.5 mbar. To evaluate the effect of Al addition to Fe-Mn-Al alloy, the Archimedes principle and Vickers hardness were applied to estimate the density and hardness of the compact alloys. Moreover, the high-temperature oxidation resistance of the alloy was evaluated at 800 °C for 8 cycles. The structure of the alloy before and after oxidation was studied by means of X-Ray Diffractometer and SEM-EDS. The XRD analysis results show that the FeMn-0Al alloy is mainly composed Fe3Mn7 phase, the presence of FeAl phase at 3 wt% Al, and Al8Mn5 phase at 5 wt% Al. The density and hardness of Fe-Mn-Al alloys decreased with the increased Al content. Fe-Mn-Al alloy without Al addition exhibits poor oxidation resistance since the first cycle of the test. The results of microstructural analysis showed that although the alloy with the addition of 3 wt% Al showed less mass gain after being exposed for 8 cycles at 800 °C, the Fe-Mn-Al alloy with 5 wt% tended to be more resistant to oxidation and had no cracking defects. The structure of the oxide formed on the surface of the alloy is composed of two layers (ie; outer and inner layer) which are affected by each alloy composition.